(untitled) (Linguostylistic Studies, 2016)
The article deals with the basic content, pragmatic and stylistic features of publisistic narrative. The main attention is paid to the notion of narrative strategy as a defining principle of structuring the text of a newspaper article. The narrative is defined as a text (in a broad sense) or a number of texts which describe socially important events in the sequence of their deployment and which are constructed in accordance with certain language and content models. The elements of newspaper narrative include: 1) eventfulness, 2) events presentation sequence or chain of scenes, 3) temporality, 4) the experience of perception. One more factor which determines the content of the narrative is its referentiality to objects that exist only in the real world. The author argues that the mass media texts in their bulk contribute to the formation of social memory. Key words: narrative, narrative strategy, newspaper article, event. References